The Character and Function of the Temple Metaphor (ναός) in the Corinthian Correspondence - Kowalski, Marcin (The Biblical Annals, 2025)
Applying the term of conceptual metaphor, the author examines Paul’s use of the temple metaphor to describe individual believers and the community of the Church in 1 Cor 3:16–17, 6:19, and 2 Cor 6:16. He begins with a concise overview of the numerous Pauline texts in which the temple-related vocabulary is applied to describe Christ and the Christian. Turning to the Corinthian correspondence, in which the term ναός occurs, the author places 1 Cor 3:16–17, 6:19, and 2 Cor 6:16 in their argumentative context and points to their common features. Among them, he mentions problems in Corinth, the individual and communal character of the temple metaphor, the apostle’s appeals for unity in the Church, for the Church to break with sin, and embrace his gospel. The correlates of the temple that Paul applies to believers are God’s saving presence, holiness, purity, worship, and the punishment that awaits those who destroy God’s temple. Finally, the author examines Paul’s use of the temple metaphor to shape the new identity of believers, comparing it to the use of the temple metaphor in Qumran writings.